Safety and efficacy of astaxanthin‐dimethyldisuccinate (Carophyll® Stay‐Pink 10%‐CWS) for salmonids, crustaceans and other fish. (18th December 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of astaxanthin‐dimethyldisuccinate (ATX‐DMDS) for salmonids, crustaceans and other fish. The applicant has provided evidence that ATX‐DMDS currently on the market complies with the conditions of authorisation for salmon and trout. ATX and ATX‐DMDS are safe for salmonids, crustaceans and fish up to 100 mg ATX/kg complete diet, corresponding to 138 mg ATX‐DMDS/kg. The FEEDAP Panel re‐assessed the toxicological profile of ATX based on data already considered in 2014, the literature review performed by the applicant and the data available in the context of an EFSA public call for data on ATX. The acceptable daily intake (ADI) of 0.2 mg astaxanthin/kg body weight (bw) per day obtained by applying an uncertainty factor of 200 to a lowest observed adverse effect level (LOAEL) of 40 mg/kg bw per day for the increased incidence of multinucleated hepatocytes observed in a 2‐year carcinogenicity study replaces the one of 0.034 mg/kg bw established by the FEEDAP Panel in 2014. The use of ATX‐DMDS in the nutrition of salmonids, other fish and crustaceans up to the maximum permitted dietary level is of no concern for the safety of the consumer. No dermal or ocular risk for the users is likely to occur under practical conditions. In the absence of inhalation toxicology study, the Panel is not in the position to establish the inhalation toxicity of the additive. The use of synthetic ATX‐DMDS does not pose a significant additional risk to the environment compared with natural astaxanthin. ATX‐DMDS is efficacious in colouring the flesh of salmonids and other fish. ATX‐DMDS is an effective pigment for crustaceans at the proposed conditions of use.